Do emotions bring customers to an environment: Evidence from Pakistani shoppers? - Saira Aziz; Waseem Bahadur; Salman Zulfiqar; Binesh Sarwar; Khurram Ejaz Chandia; Muhammad Badr Iqbal (Cogent Business & Management, 2018)
The purpose of this study is twofold: First, it examines the impact of emotional states and shopping evaluations on customers' store choice intentions before entering the store; second, what atmospheric factors and shopping value evaluations affect customers' emotions after entering the store, which, in turn, influence their final choice decision? To test the proposed hypothesis, data were collected in Pakistan from the real-life customers at a specialty apparel store. Exploratory factor analysis (EFA) and structural equation modeling (SEM) were performed to analyze the data results. Study results disclose that the customers do experience pleasure before being exposed to any environment. The utilitarian value and hedonic value positively affect the store choice intentions of customers before entering a store. While the in-store environmental stimuli influence the pleasure and arousal experienced after entering the store, which, in turn, affects customers' store choice decisions. This particular study adds to the literature by quantitatively studying the impact of emotional states on customer store choice decisions before entering a store, and it also inspects the change in emotions after entering the store in the presence of three component environmental factors such as ambient factors, design factors, and social factors and customers' shopping value evaluations. Therefore, retail managers should consider managing customer feeling states by providing favorable in-store environments, because negative store experience can even ruin the positive feelings customer may have before coming to the store for shopping and experiencing.
Keywords: 650